PROFESSORES HOMENS NA EDUCAÇÃO DE CRIANÇAS DE 3 E 4 ANOS: narrativas infantis - Raquel Quintina Pereira Bard (2025)
This dissertation is the result of a master's degree research project, originating from the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul (UFMS), submitted to the Research Line: Education, Culture and Society. The research is linked to the project “Educational relations from the perspective of educational actors: weaving narratives of children and teachers in training”, being developed by researchers who are members of the Study and Research Group on Formative Narratives (Gepenaf) of the School of Education at UFMS. The object of study of this research is the male presence in early childhood education, from the perspective of children, with the objective of understanding children's perception of the presence of male teachers in early childhood education. The research is based on the Biographical Method, based on authors such as Franco Ferrarotti and Christine Delory-Momberger, on childhood studies, with Moysés Kullmann Junior, Phillip Ariès, Willian Cosaro and Manuel Jacinto Sarmento, and on children's narratives, based on studies by Maria da Conceição Passeggi and Ecleide Cunico Furlanetto. The study includes an analysis of the history of the teaching profession and the feminization of teaching, the concept of childhood and the child as a subject with rights. To produce data, the following were carried out: literature review, production of the state of the issue, documentary research, participant observation and discussion groups with ten children between 3 and 4 years old, from a preschool class in the Municipal Education Network of Campo Grande. The narratives were recorded through notes in a field diary and audio and video recordings. The results show a deeper discussion about teacher training, the relationship between welfare and education and the role of children. The children's narratives revealed that the presence of male teachers in early childhood education is perceived in different ways by the children who participated in the study, influencing their gender identities and social dynamics. The children associated positive characteristics with the male figure, showed that they felt safe, protected and cared for, free to show affection and care, and receptive to learning through playful activities (such as dance, music, games). However, their perceptions also reflect prejudices and gender stereotypes, as they brought into their narratives the idea that male teachers cannot perform functions related to their intimate hygiene, such as changing diapers or bathing, as they considered this to be a feminine activity, or when they found it funny that the teacher wore a cap and apron when developing an activity with a recipe. It can be concluded, based on the results, that the use of children's narratives contributes to the understanding of school culture, as well as the influence of adults (at school and in the family) on children's views regarding the relationship between gender, profession and social roles. This reinforces the emergence of an attentive and respectful look at childhood, understanding children as historical subjects who can contribute to rethinking educational models, curricula and the ways in which schools for children are organized.